2023
DOI: 10.1002/jcb.30390
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer‐derived exosomes facilitate pulmonary metastasis by activating ERK‐mediated immunosuppressive macrophage polarization

Abstract: Gastric cancer (GC) with pulmonary metastasis is one of the deadliest diseases in the world; however, the underlying pathological mechanisms and potential therapeutic targets remain to be elucidated. As exosomes play indispensable roles in the formation of premetastatic niches (PMN) and cancer metastasis. Therefore, investigating the underlying mechanisms of exosome-mediated pulmonary metastasis of GC may shed new light on identifying novel therapeutic targets for GC treatment. GC-derived exosomes were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…It was reported that tumor‑derived exosomes were able to promote the secretion of CCL1 by lung fibroblasts, which in turn resulted in differentiation of regulatory T cells (Tregs) via activating its specific receptor CCR8 and establishment of an immunologically tolerant PMN [ 274 ]. Moreover, two independent studies have uncovered that tumor-derived exosomes can induce upregulation of PD-L1 through different mechanisms to drive polarization of lung immunosuppressive macrophages, thereby promoting the formation of immunosuppressive PMN [ 275 , 276 ]. In addition to their effects on cellular components of immune microenvironment, tumor-derived exosomes were also demonstrated to activate alveolar epithelial Toll-like receptor 3 (TLR3) to recruit neutrophils, which led to formation of lung PMN [ 277 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…It was reported that tumor‑derived exosomes were able to promote the secretion of CCL1 by lung fibroblasts, which in turn resulted in differentiation of regulatory T cells (Tregs) via activating its specific receptor CCR8 and establishment of an immunologically tolerant PMN [ 274 ]. Moreover, two independent studies have uncovered that tumor-derived exosomes can induce upregulation of PD-L1 through different mechanisms to drive polarization of lung immunosuppressive macrophages, thereby promoting the formation of immunosuppressive PMN [ 275 , 276 ]. In addition to their effects on cellular components of immune microenvironment, tumor-derived exosomes were also demonstrated to activate alveolar epithelial Toll-like receptor 3 (TLR3) to recruit neutrophils, which led to formation of lung PMN [ 277 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…High-throughput sequencing showed that miR-92a-3p was added to GC-exo and activated ERK signaling by inhibiting PTEN expression. Inhibition of ERK signaling with PD98059, a specific inhibitor, notably suppressed PD-L1 expression in macrophages and reversed the immunosuppressive impact of PMN, greatly inhibiting GC cell colonization in the lung ( 129 ).…”
Section: Application Of Tams In Gcsmentioning
confidence: 99%
“…These EVs activated the ERK signaling pathway, induced immune-suppressive phenotypic differentiation of macrophages, increased PD-L1 expression, and promoted lung metastasis of GC. Furthermore, inhibition of the ERK signaling pathway with PD98059 significantly reduced PD-L1 expression in macrophages and inhibited the colonization of GC cells in the lungs ( Gu et al, 2023 ). EVs can promote M2 polarization of macrophages, and can also inhibit M2 polarization.…”
Section: Evs Influence the Metastasis Of Gc By Modulating Immune Resp...mentioning
confidence: 99%